Analisis Perma Nomor 1 Tahun 2020 dalam Kaitannya dengan Penanggulangan Tindak Pidana Korupsi - Hariri Lubis, Agustiar; Mutiara Nelson , Febby (Dinasti Review Publisher, 2024)
Corruption crimes that have occurred so far seem to have taken root everywhere, not only causing financial loss to the state, but also a violation of the social and economic rights of the community. Corruption in Indonesia has become a systemic crime and is increasing every year. Therefore, this article will discuss overcoming criminal acts of corruption in Indonesia. This research uses normative juridical methods by examining research materials from Supreme Court Regulation Number 1 of 2020 concerning Sentencing Guidelines Article 2 and Article 3 of the Corruption Eradication Law. The results of this research indicate that the effort to overcome criminal acts of corruption through the Perma Sentencing Guidelines is to clarify the sanctions that must be imposed on the perpetrators so that the Judge in making his considerations can be focused. However, the Perma on Sentencing Guidelines is not adequate because the Supreme Court does not have the authority other than to regulate prison sentences and fines. This regulation also only applies to perpetrators of criminal acts of corruption who violate the provisions of Article 2 and Article 3 of the PTPK Law.